IDENTIFIKASI MAKROZOOBENTOS SEBAGAI BIOINDIKATOR KUALITAS PERAIRAN DI PANTAI TELUK BENOA, BADUNG - Sutrisnawati, Eka Ari; Arthana, I Wayan; Windia Adnyana, Ida Bagus (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2023)
Utilization of coastal waters for aquaculture activities or for other activities provides positive value for human welfare but can also provide the potential for reducing water quality. The decline in environmental quality can be seen from changes in components such as biology, chemistry, and beach physics. Changes in chemical and physical components cause sediment to decrease, which will affect the life of marine biotas, such as the community structure, especially the slow-moving and relatively settled biota on the bottom of the waters (macrozoobenthos). Macrozoobenthos are very appropriate to be used as an indicator of changes in water quality due to their benthic nature which is relatively silent or has low mobility so it is strongly influenced by the environment. The purpose of the study was to determine the structure of the macrozoobenthos community and the condition of seawater quality. There were 25 species of gastropods and 3 other classes. The macrozoobenthos species diversity index on the Benoa Bay Coast showed a moderate level of diversity with the highest value of 2.4576. The uniformity index at each station ranges from 0.0894 – 0.5337. The value of the dominance index ranges between 0.000004-0.7656. Based on the relative abundance, the macrobenthos community is dominated by the Gastropod class. The temperature values ??at each station were relatively the same, ranging from 29.3°C– 30.8°C, and the pH was in accordance with quality standards for macrozoobenthos growth. Some indicators of water quality are still below the quality standard threshold, but the concentration of phosphate (PO 4 ) at all locations is already above the predetermined quality standard of 0.015 mg/L ? . Keyword: Macrozoobenthos; Bioindicator; Benoa Bay; Bali